Peribahasa Sunda Sebagai Refleksi Pola Pikir Masyarakat Sunda - Dewi Kusuma (AL-BURHAN, 2022)
This study analyzes the mindset of the Sundanese people contained in proverbs. Sources of data collected in this study from a book entitled Peperenian Urang Sunda by Rahmat Taufiq Hidayat et al. The method used in this study is a qualitative descriptive method with a semiotic approach to Roland Barthes. The purpose of this study is to determine the mindset of the Sundanese people implied in proverbs. Data analysis was carried out by examining the meaning of denotation and connotation. The results of the analysis show that the mindset of the Sundanese people describes the characteristics of Sundanese people such as cageur (healthy), bageur (good), bener (true), singer (self-aware), wanter (brave), and pinter (intelligent).